Complete revascularization in STEMI with multivessel disease: how late is too late?. (26th April 2021) - Ferreira, J; Costa, C; Fonseca, M; Farinha, JM; Esteves, AF; Pinheiro, A; Coelho, R; Caria, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Recent research has shown that in patients (pts) with ST-elevation myocardial infarction (STEMI) and multivessel coronary disease, revascularization of non-culprit lesions soon after primary percutaneous coronary intervention (PCI) reduces the risk of death and myocardial infarction (MI) compared with culprit-lesion-only PCI. However, in real-world practice, centres often cannot perform PCI of non-culprit lesions as early after hospital discharge as reported in these studies.  Purpose: To analyse current treatment of STEMI with multivessel disease in a district hospital and determine if there is still benefit in doing complete revascularization (CR) even when non-culprit lesion PCI is done late after hospital discharge.  Methods: We conducted a retrospective pilot study including all consecutive pts with STEMI submitted to primary PCI in a district hospital in 2018 who presented angiographically significant multivessel disease amenable to PCI. We compared outcomes between pts who underwent CR after hospital discharge (study group), those who did it during hospitalization and the group who only underwent culprit-lesion PCI.  Exclusion criteria included history of coronary bypass graft, cardiogenic shock at admission, a chronic total occlusion as single non-culprit lesion and death before treatment strategy was defined. Results: Of the 302 pts treated for STEMI in 2018, 125 had multivessel disease. Of these, 27 met exclusion criteria, resulting in a sample of 98 pts with a mean age of 66 years. Median time from symptom onset to PCI was 5 hours, with 8% of pts presenting in Killip class II-III. Most pts (61%) underwent CR during index hospital stay. 15% underwent PCI of non-culprit lesions after hospital discharge, with a median time from primary to non-culprit PCI of 86 days. Finally, 18% underwent no further revascularization. An additional 5 pts had non-culprit lesions treated surgically after a median of 364 days. At a median follow-up of 2.4 years, death had occurred in none of the pts of the study group, which did not significantly differ from the 7 pts (12%) in the group revascularized at index hospitalization (log-rank test: p = 0.185) but was significantly inferior to the 5 (29%) in the culprit-only PCI group (p = 0.037). There was no significant difference in a composite outcome of death, MI and stroke. The secondary outcome of ischaemia-driven revascularization occurred more often in the study group compared with those revascularized during hospitalization (HR 6.68; 95% CI 1.09-41.01; p = 0.040).  Conclusions: This study suggests that complete revascularization in STEMI with multivessel disease even late after hospital discharge is still superior to culprit-lesion only PCI in reducing risk of death. On the other hand, this late revascularization seems to be associated with higher rates of ischaemia-induced revascularization. Further research with a larger sample will be required to confirm the results of this pilot study.